Histomorphological and Histochemical Study of the Skin of the Local Dog . - Rabab Naser (Basrah Journal of Veterinary Research)
The present study aimed to identify the skin features of the local dog. After anesthesia, five adult dogs took the skin samples, and the wounds were sutured that form after collecting the sample and the samples were fixated with 10% formalin and Bouin's solution.(special stain )in the present study, the skin consists of two layers epidermis and dermis, the epidermis is composed of epithelial cell layers comprised of four different types of cells of various studied regions. while the dermis was composed of two layers that embedded the hair follicles, sebaceous glands, and a few numbers of sweet and sebaceous glands associated with hair follicles. In conclusion, The skin is a large organ covering all body joints, underlying the muscles and bones. It is characterized by a few sebaceous and sweat glands.